Modeling of femoral head aseptic necrosis in Wistar rats - N. A. Shabaldin; A. V. Shabaldin; N. E. Popova; A. V. Postnikova; L. A. Bogdanov; A. V. Tsepokina (Фундаментальная и клиническая медицина, 2022)
Aim. To develop an animal model of femoral head aseptic necrosis for studying Legg–Calvé–Perthes disease.Materials and Methods. To induce the development of aseptic necrosis, we used Wistar rats (n = 8) which suffered from combined hypoperfusion of the femoral head and increased intra-articular pressure in the hip joint. Having employed isoflurane anesthesia, we performed an incision (≈ 3 cm length) on the outer surface of the thigh in the projection of the hip joint and then excised periosteum in the proximal third of the femur. A dense vicryl ligature was applied around the femoral neck to reduce blood perfusion of the femoral head. Further, 1.5 mL 2% rheopolyglucinum solution (10% isotonic dextran, 30-40 kDa molecular weight) was injected into the hip joint cavity to increase intra-articular pressure. Rats were sacrificed upon 8-week follow-up with subsequent X-ray and histological examination.Results. Our animal model of femoral head aseptic necrosis includes two main components of Legg–Calvé–Perthes disease: an increase in the intra-articular pressure and insufficient blood perfusion of the femoral head. In all (8/8) cases, aseptic necrosis of the femoral head was achieved. Eight weeks post intervention, the condition of the proximal femur 8 was similar to impression fracture.Conclusion. Our model of femoral head aseptic necrosis fully reflects the pathogenesis of LeggCalve-Perthes disease and can be therefore used in experimental studies.